HARMONIZATION OF ASEAN INVESTMENT LAWS: ANY POSSIBILITY TOWARD RECOGNITION AND ENFORCEMENT OF FOREIGN JUDGMENTS IN ASEAN MEMBER STATES - U-Krisdh Musicpunth; Anon Sriboonroj (Universitas Bengkulu, 2018)
In having ASEAN investment related agreements responded to economic activities seeking by investor and service providers or suppliers practically, harmonization of investment related laws among AMS is from time to time reiterated “necessarily needed in various aspects”. Since establishment to operation and dispute settlement are under the concept of ASEAN free movement, the host country normally shapes up all processes of doing business by its domestic laws and regulations. Of course, they are depended on each member state’s regime and jurisdiction which always different from each other and in principle not apply cross borders. The ten members we already have with sovereignty issue in addition, these make the need of integrity of laws moved even harder. Recommended by the authors as an optional choice, recognition and enforcement of foreign judgments, inter-alia, can play its role as a supportive mechanism under harmonization of investment laws. The legal relationship between investors and investors, investors and states or between states and states in AMS then will be undertaken regionally and seamlessly.